A large‐scale proteogenomics study of apicomplexan pathogens—Toxoplasma gondii and Neospora caninum. Issue 15 (15th May 2015) - Krishna, Ritesh; Xia, Dong; Sanderson, Sanya; Shanmugasundram, Achchuthan; Vermont, Sarah; Bernal, Axel; Daniel‐Naguib, Gianluca; Ghali, Fawaz; Brunk, Brian P.; Roos, David S.; Wastling, Jonathan M.; Jones, Andrew R.
<x xml:space="preserve">Abstract</x> Proteomics data can supplement genome annotation efforts, for example being used to confirm gene models or correct gene annotation errors. Here, we present a large‐scale proteogenomics study of two important apicomplexan pathogens: Toxoplasma gondii and Neospora caninum. We queried proteomics data against a panel of official and alternate gene models generated directly from RNASeq data, using several newly generated and some previously published MS datasets for this meta‐analysis. We identified a total of 201 996 and 39 953 peptide‐spectrum matches for T. gondii and N. caninum, respectively, at a 1% peptide FDR threshold. This equated to the identification of 30 494 distinct peptide sequences and 2921 proteins (matches to official gene models) for T. gondii, and 8911 peptides/1273 proteins for N. caninum following stringent protein‐level thresholding. We have also identified 289 and 140 loci for T. gondii and N. caninum, respectively, which mapped to RNA‐Seq‐derived gene models used in our analysis and apparently absent from the official annotation (release 10 from EuPathDB) of these species. We present several examples in our study where the RNA‐Seq evidence can help in correction of the current gene model and can help in discovery of potential new genes. The findings of this study have been integrated into the EuPathDB. The data have been deposited to the ProteomeXchange with identifiers PXD000297and PXD000298.